„Duch czasu wycisnął jednak na tej pracy swe piętno”. Historia Zagłady w badaniach Żydowskiego Instytutu Historycznego w okresie stalinowskim - Stach, Stephan (Zagłada Żydów. Studia i Materiały, 2017)
The Jewish Historical Institute in Warsaw was probably the only research institution in the Soviet Bloc and one of very few that undertook research on the Shoah during the 1950s. This article analyses the institute’s research and working conditions against the background of the general political regime under Stalinism in Poland. It argues that despite sometimes heavy-handed political biases in its publications, the institute made an important contribution to research on the Shoah. Its work also came to the attention of Jewish centers outside the Soviet Bloc, though it was seen through the prism of the Cold War.